The Clinical Chemistry of Laboratory Animals - Loeb, Walter F;Ed. Quimby, Fred W;Ed (Taylor & Francis, 1999)
Designed to aid laboratory animal veterinarians, clinical chemists, toxciologists, clinical pathologists, and other biomedical investigators in the selection and interpretation of clinical chemistry studies on specimens from laboratory animals. The resource also guides the investigator in the evaluation of organs and systems of laboratory animals.